Challenges for achieving safe and effective radical cure of P. vivax – a round table discussion of the APMEN Vivax Working Group - Thriemer, K; Ley, B; Bobogare, A; Dysoley, L; Alam, M; Pasaribu, A; Sattabongkot, J; Jambert, E; Domingo, G; Commons, R; Auburn, S; Marfurt, J; et al. (BioMed Central, 2017)
The delivery of safe and effective radical cure for Plasmodium vivax is one of the greatest challenges for achieving malaria elimination from the Asia-Pacific by 2030. During the annual meeting of the Asia Pacific Malaria Elimination Network (APMEN) Vivax Working Group in October 2016, a round table discussion was held to discuss the programmatic issues hindering the widespread use of primaquine (PQ) radical cure. Participants included 73 representatives from 16 partner countries and 33 institutional partners and other research institutes. In this review the key discussion points are presented and grouped into five themes: (i) current barriers for glucose-6-phosphate deficiency (G6PD) testing prior to PQ radical cure, (ii) necessary properties of G6PD tests for wide scale deployment, (iii) the promotion of G6PD testing, (iv) improving adherence to PQ regimens and (v) the challenges for future tafenoquine (TQ) roll out. Robust point of care (PoC) G6PD tests are needed, which are suitable and cost-effective for clinical settings with limited infrastructure. An affordable and competitive test price is needed, accompanied by sustainable funding for the product with appropriate training of healthcare staff, and robust quality control and assurance processes. In the absence of quantitative PoC G6PD tests, G6PD status can be gauged with qualitative diagnostics, however none of the available tests is currently sensitive enough to guide TQ treatment. TQ introduction will require overcoming additional challenges including the management of severely and intermediately G6PD deficient individuals. Robust strategies are needed to ensure that effective treatment practices can be deployed widely, and these should highlight the caveats as well as the benefits of radical cure for both the patients and the community. Widespread access to quality controlled G6PD testing will be critical.